Stepwise approach to a large fibroid uterus in a nulliparous woman: a case report - Nahar, Kirty; Hiremath, Gayatri; Nahar, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Leiomyomas are the most common benign pelvic tumour in the reproductive age women accounting for almost 20-25% incidence in general population. Leiomyomas are monoclonal tumours of the smooth muscle cells of the myometrium containing varying amount of fibrous tissue. A 45-year-old, unmarried, nulliparous woman presents with large distended abdominal swelling and heavy bleeding during her periods at a tertiary care hospital. This case report magnifies varying risk factors, diagnosis and management of large uterine fibroids and highlights joint diagnosis and decisions of gynaecologist, radiologist and pathologist. After putting forth various modes of treatment options, the definitive treatment was decided considering her age, severity of symptoms, that is fibroid impacting her quality of life and her future parity interest. This particular case showcases successful preoperative medical treatment, timely investigations and planned surgery for optimal patient outcome.